Kinetics of oxalate degradation in aerated packed-bed biofilm reactors under nitrogen supplemented and deficient conditions - Weerasinghe Mohottige, T.; Kaksonen, A.; Cheng, K.; Sarukkalige, Priyantha Ranjan; Ginige, M. (Elsevier, 2019)
© 2018 Elsevier Ltd Destruction of oxalate from alumina-refining process liquor is considered essential for many alumina refineries around the world. Some refineries have embraced the use of aerobic bioreactors as a cost-effective destruction method. These processes are often supplemented with an external nitrogen (N) source to facilitate microbial activity, even though such augmentations are undesirable due to increase of operational costs. Until now, there has also only been little information on oxalate degradation kinetics, although this knowledge is essential to design bioreactor processes. Hence, this study aimed at determining oxalate degradation kinetics in two aerobic packed bed biofilm reactors under both N–supplemented and N-deficient conditions. Michaelis-Menten equation was used to derive kinetic parameters for specific oxalate degradation. The N-deficient culture had a higher affinity (Km of 458.4 vs. 541.9 mg/L) towards oxalate and a higher maximum specific oxalate removal rate (Vmax of 161.3 vs. 133.3 mg/(h·g biomass)) compared to the N-supplemented culture, suggesting that the N-deficient culture is better suited to remove oxalate. Microbial community analysis also showed differences in the composition of the two cultures. Based on the kinetic parameters derived, a novel two step oxalate removal process was proposed that capitalises on higher specific oxalate removal rates for efficient oxalate destruction from waste streams of alumina industry.